Determinant of adverse early neonatal outcomes following emergency cesarean section in North West, Ethiopia: institutional-based case-control study - Beyene Sisay Damtew; Alemu Merga Hailu; Bezawit Melak Fente; Tadesu Wondu Workneh; Hinsermu Bayu Abdi (BMC Pregnancy and Childbirth)
Abstract Background The World Health Organization recommends a cesarean delivery rate of 5–15%, which is thought to be within the range that can reduce infant morbidity and mortality. Various investigations have shown that those poor newborn outcomes are influenced by a variety of maternal and fetal factors and are more prevalent in emergencies than planned cesarean deliveries. Ethiopia is one of the five nations that account for 50% of all neonatal fatalities worldwide. Sub-Saharan African countries account for 38% of all infant deaths worldwide. Aim To know the determinants of adverse early neonatal outcomes after emergency cesarean delivery. Method and material A multicenter case-control study design would be carried out between November 2022 and January 2023. Using the consecutive method, a sample of 318 mother-newborn pairs was studied. Direct observation and face-to-face interviews were undertaken to gather the data using a semi-structured questionnaire. For both data input and analysis, Epi Data version 4.6 and Stata version 14 software were used. Both the crude and adjusted odds ratios were computed. The measure of significance was based on the adjusted odds ratio with a 95% confidence interval and a p-value of less than 0.05. Results Maternal age over 35, the presence of danger signs during pregnancy, and non-reassuring fetal heart rate were significantly associated with increased risk of adverse fetal outcomes following emergency cesarean section. Women aged over 35 were 3.6 times more likely to experience adverse fetal outcomes compared to younger women (AOR: 3.6, 95% CI: 1.1, 9.7). Women with danger signs during pregnancy were 3.5 times more likely to have adverse fetal outcomes compared to those without (AOR = 3.5, 95% CI: 2.4, 36). Similarly, cases with non-reassuring fetal heart rate were associated with a 5.2 times higher risk of adverse newborn outcomes (AOR = 5.2, 95% CI: 1.1, 26). Conclusion This study identified advanced maternal age (over 35 years old), pregnancy complications, and non-reassuring fetal heart rate as significant risk factors for adverse neonatal outcomes following emergency cesarean section.